2003
DOI: 10.2118/03-10-04
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Sand Production Through Horizontal Well Slots in Primary Production

Abstract: Cold production in unconsolidated heavy oil reservoirs, where sand production is encouraged (CHOPS), has proven to be successful for vertical wells. However, the application of CHOPS to horizontal wells has been less profitable due mainly to excessive sand cleanout costs. Therefore, reducing sand cleanout costs by controlling sand production into horizontal wells while enhancing the surrounding permeability of the formation is an important factor in optimizing cold production from unconsolidated heavy oil rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The pressure at the entrance of the slot ( p slot ) must be calculated in order to calculate (dp/dL) 11,slot . A detailed description of this calculation can be found in Meza-Díaz et al (2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure at the entrance of the slot ( p slot ) must be calculated in order to calculate (dp/dL) 11,slot . A detailed description of this calculation can be found in Meza-Díaz et al (2003).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous experimental investigation using synthetic and idealized materials (Meza-Díaz et al 2003), differences observed in sand-production behavior were attributed to differences in grain-size distribution. The SW/ EGD ratio (SW/D i ), particularly for the D 99.9 diameter, was identified as an important parameter in sand production through slots.…”
Section: Pressure Gradient Identificationmentioning
confidence: 99%
“…An analysis of the sand-production data from the previous air tests indicated that there was no obvious trend between sand production and the sorting of the sand (as represented by the uniformity coefficient) or between sand production and the sandgrain morphology (Meza-Diaz et al 2003, 2004. This is shown graphically in Figs.…”
Section: Experimental Conditions and Parameter Selectionmentioning
confidence: 93%
“…The results of previous sand-production experiments using air as the working fl uid (Meza-Diaz et al 2003, 2004 were used to guide the selection of the range of slot widths for the experiments reported in this study. The air tests provided sand-production data across several slot sizes for various sands that possessed different grain-size distributions and morphologies (shapes).…”
Section: Experimental Conditions and Parameter Selectionmentioning
confidence: 99%
“…• Although counterintuitive, spherical proppants have been found to be more stable in laboratory tests examining the flowback of particles into horizontal-well slots (Meza et al 2002;Meza-Diaz et al 2003).…”
Section: Proppant Flowbackmentioning
confidence: 99%